Analisis Penghematan Penggunaan Energi Listrik Berbasis Fuzzy pada Hotel - Rifqi Wibowo; Sri Artini Dwi Prasetyowati; Agus Adhi Nugroho (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Electricity is an important necessity, but its use must be managed wisely to avoid waste and negative environmental impacts. Energy-saving programs implemented in buildings encourage consumers to use energy more efficiently, reduce wasteful consumption that leads to inflated electricity bills, and serve as an initial step in overall energy management to lower total energy costs. Hotel Grand Dian Bumiayu showed an initial IKE of 27.77 kWh/m²/year. This figure, with a total energy consumption of 144,752.01 kWh/year, falls into the highly efficient category. This means the building's energy usage is already considered optimal compared to existing standards. Fuzzification calculations, using data from September 2023, yielded a DeFuzzification value of 12.858. This value is within the IKE range for the "Moderately Efficient" criterion (12.08 – 19.17), meaning that, based on this analysis, energy usage during that period was classified as moderately efficient. A detailed energy audit identified four types of loads that significantly contributed to the hotel's power consumption. From this analysis, it was revealed that the largest electricity consumption (kWh/year) originated from the air conditioning system, accounting for 77%. Following the air conditioning system, the lighting system ranked second with 14% of the total consumption. Then, office equipment contributed 5%, and the smallest electricity consumption was recorded for utilities, at 4%. After implementing Energy Saving Opportunities (PHE), the final Energy Consumption Intensity (IKE) was recorded at 30,013.75 kWh/m²/year. This IKE value indicates that energy consumption is highly efficient. This result is quite reasonable, considering that the initial IKE even before the analysis of energy-saving opportunities was conducted, was already in the efficient category.